2017
DOI: 10.1007/s10695-016-0306-3
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish phosvitin-derived peptide Pt5 inhibits melanogenesis via cAMP pathway

Abstract: Zebrafish phosvitin-derived peptide Pt5, consisting of the C-terminal 55 residues of phosvitin, has been shown to have an antimicrobial-immunomodulatory activity comparable to phosvitin. Here, we showed clearly that Pt5 had the capacity to inhibit tyrosinase (TYR) activity and melanin biosynthesis, and this inhibition was independent of cell proliferation and cytotoxic effects. Incubation of fluorescein isothiocyanate (FITC)-labeled Pt5 with B16F10 melanoma cells revealed that Pt5 was localized in the cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…It has been speculated that the inhibitory effect of Pt5 was associated with the presence of polar and uncharged amino acid residues, serine, and arginine in its structure. There was no reduction in cell proliferation in the MTT assay on B16F10 melanoma cells 49 …”
Section: Natural Peptidesmentioning
confidence: 84%
See 1 more Smart Citation
“…It has been speculated that the inhibitory effect of Pt5 was associated with the presence of polar and uncharged amino acid residues, serine, and arginine in its structure. There was no reduction in cell proliferation in the MTT assay on B16F10 melanoma cells 49 …”
Section: Natural Peptidesmentioning
confidence: 84%
“…There was no reduction in cell proliferation in the MTT assay on B16F10 melanoma cells. 49 Liang et al reported that collagen peptides from milkfish scales (MSCP) had whitening effects on skin by chelating of tyrosinase copper (IC 50 = 752.4 μg/m); however, no details on the sequences were reported. 50 Nie et al used phage displaying technique and found a heptapeptide (Ile-Gln-Ser-Pro-His-Phe-Phe) that could inhibit tyrosinase with IC 50 s = 1.7 and 4.0 mM for monophenolase and diphenolase, respectively.…”
Section: Kawagishia Et Al Drew Out Anti-tyrosinase Cyclotetrapeptide Frommentioning
confidence: 99%
“…Melanin is an effective absorber of light, capable of protecting human skin from damage caused by UV radiation [18]. Melanogenesis plays a critical role in protecting skin against external stresses such as UV irradiation and oxidative stressors [19].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of pigmentation-related genes such as tyrosinase, TRP1, and TRP2 is mediated by MITF [19,29]. MITF is well known as the master regulator of melanin synthesis [18,30] and controls several key mechanisms including pigmentation, dendricity, and proliferation in response to environmental factors such as UV radiation [31].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, phosvitin and the phosphopeptides generated from its enzymatic hydrolysis exhibit high antioxidant activities [4,[10][11][12]. Phosvitin is also recognized for its antimicrobial activity [13], its action against melanogenesis [14][15][16], and its ability to improve the bioavailability of calcium in the intestine and the absorption of calcium by bones [17][18][19][20]. Some studies have also investigated the emulsifying properties of phosvitin [10,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%